Amyloid cardiomyopathy - Karafiatova, Lucie; Pika, Tomas (Biomedical papers, 2017)
Amyloidosis is a heterogeneous group of diseases characterized by the deposition of amyloid. It is caused by extracellular deposition of insoluble fibrils with beta-pleated sheet configuration. The protein misfolding abnormalities result in amyloid fibrils and may manifest as primary, secondary, or familial amyloidosis. Amyloid deposition can occur in multiple organs (eg, heart, liver, kidney, skin, eyes, lungs, nervous system) resulting in a variety of clinical manifestations. Cardiac involvement can occur as part of a systemic disease or as a localized phenomenon. Cardiac involvement in all types of amyloidosis represents a major negative prognostic factor. Early diagnosis, multi-disciplinary cooperation and proper therapy are key aspects of care for patients with amyloid cardiomyopathy. Early diagnosis is crucial, especially in AL amyloidosis, as patients with advanced heart disease are unsuitable candidates for modern, effective hematological treatment including autologous stem cell transplantation. Despite signal development in diagnostics and therapy, the prognosis for patients with advanced cardiac involvement remains poor. This article is an overview of amyloidosis, providing information about the characteristics of cardiac amyloidosis, and present a structured approach to diagnosis, treatment and prognosis of this condition.
Keywords: amyloidosis; amyloid cardiomyopathy; heart diseases; heart failure; restrictive cardiomyopathy